Orientalisme Dan Oksidentalisme: Kajian Keotentikan Al-Qur’an - batubara, mardiyah nur (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Orientalism sees the East as the other, so Oksidentalism aims to unravel the ambiguous historical knot between the ego and the other, and the dialectic between the complexity of inferiority on the ego and the complexity of superiority on the other. Old Orientalism is the view of the European ego, the subject of study of the object under study.. Oksidentalism wants to demand liberation from the grip of orientalist colonialism. Oksidentalism this time is built on a neutral ego and has no ambition to seize power, and only wants liberation. He also did not want to discredit other cultures, and only wanted to know the formation and structure of Western civilization. The ego of Oksidentalism is considered to be cleaner, objective, and neutral compared to the ego of Orientalism. Orientalist studies on the authenticity of the Qur'an seem to provoke reactions from Muslims (oksidentalism). as well as the criticism of Fazlur Rahman and al-'Azami against the orientalists.